Karakter Morfometrik Barbodes schwanenfeldii di Sungai Rupit Sumatera Selatan - Fatiqin, Awalul; Amallia, Ra Hoetari Tirta; Dhani, Achmad Bagus (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2022)
Barbodes schwanenfeldii is a fish that lives in the waters of the Rupit River, located in Karang Jaya District, North Musi Rawas Regency, South Sumatra. The purpose of this study was to determine the morphometrics of Barbodes schwanenfeldii in the Rupit River and the differences between Barbodes schwanenfeldii fish found in other rivers. This research uses purposive sampling method. The results of morphometric measurements of Barbodes schwanenfeldii obtained in the waters of the Rupit River are smaller than the Barbodes schwanenfeldii fish found in other river waters because, fish that have habitats living in water that have experienced metal pollution in the waters of the Rupit River have an impact on growth of fish.